Reactive scattering of highly vibrationally excited oxygen molecules: Ozone formation? - Lauvergnat, D; Clary, D (1998)
A new ab initio potential energy surface based on an internally contracted multireference configuration-interaction wave function is constructed for the O2(X 3Σ-g,ν)+O2(X 3Σ-g,ν=0) →O3(X 1A1)+O(3P) reaction with ν>20. The vibrational state-to-state reaction probabilities are calculated with a time independent reactive scattering method. The state selected reactive rate constants calculated with 2D reduced dimensionality theory are very small, suggesting that the reaction of ozone formation is not significant in the O2(X 3Σ-g,ν)+O2(X 3Σ-g,ν=0) collision. © 1998 American Institute of Physics.